Additional benefit of ¹⁸F-fluorodeoxyglucose integrated positron emission tomography/computed tomography in the staging of oesophageal cancer. - Gillies, R; Middleton, MR; Maynard, N; Bradley, K; Gleeson, F (2011)
OBJECTIVE: ¹⁸F-fluorodeoxyglucose positron emission tomography (FDG PET) has been shown to improve the accuracy of staging in oesophageal cancer. We assessed the benefit of PET/CT over conventional staging and determined if tumour histology had any significant impact on PET/CT findings. METHODS: A retrospective cohort study, reviewing the results from 200 consecutive patients considered suitable for radical treatment, undergoing routine PET/CT staging comparing the results from CT and endoscopic ultrasound, as well as multi-disciplinary team records. Adenocarcinoma and squamous cell carcinoma were compared for maximum Standardised Uptake Value (SUV(max)), involvement of local lymph nodes and distant metastases. RESULTS: PET/CT provided additional information in 37 patients (18.5%) and directly altered management in 34 (17%): 22 (11%) were upstaged; 15 (7.5%) were downstaged, 12 of whom (6%) received radical treatment. There were 11 false negatives (5.5%) and 1 false positive (0.5%). SUV(max) was significantly lower for adenocarcinoma than squamous cell carcinoma (median 9.1 versus 13.5, p = 0.003). CONCLUSIONS: Staging with PET/CT offers additional benefit over conventional imaging and should form part of routine staging for oesophageal cancer. Adenocarcinoma and squamous cell carcinoma display significantly different FDG-avidity.